The potency of Plant Growth-Promoting Rhizobacteria as Biological Controller Agent of Estate Crops Diseases in The Environmentally Friendly - MESAK TOMBE (Perspektif, 2013)
Estate crops is one of the foreign exchange producers that can be relied on in the globalization era. Therefore the production of estate crops process requires means of production that is efficient and environmentally friendly to raise the competitiveness in the global market. Plant disease control by using biological  controlle agent such as PGPR is necessary to be utilized in the estate crops enterprise that is environmentally friendly and sustainable. Plant Growth-Promoting Rhizobacteria (PGPR ) is a bacterium that lives in the root and can produce antibiotic, as competitor, induce plant resistance to control pathogenic disease and pest and can secrete useful compounds  for plant growth. PGPR  user can reduce the utization of synthetic pesticide and inorganic fertilizer. The application of PGPR to control diseases in the estate crops such as pepper, tea, tobacco, and vanilla  effective to control the main pathogens such as Phytophthora capsici, Phytophthora nicotianae,Fusarium oxysporum, Pseudomonas solanacerum, Rigidoporus lignosis, Exobasidium vexans,Tobacco Mosaic Virus and nematodes. PGPR has the potency to reduce the pesticide utilization upto 50% and in the organic cultivation. PGPR has been published could complety replace the pesticide utilization especially if it is used continuously. Indonesia is the second biggest country in the biological resources including PGPR. This potency is necessary to be developed and utilized to build the estate crops that is environmentally friendly and suatainable. Key words : PGPR, biological control, environmentally friendly, induce resistance.